2019
DOI: 10.1029/2019jd031293
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Properties Over Tibetan Plateau From a Decade of AERONET Measurements: Baseline, Types, and Influencing Factors

Abstract: In this study, a decade long measurement of aerosol optical properties at two AERONET stations (Nam Co during 2006–2016 and QOMS during 2009–2017) in the Tibetan Plateau (TP), a region sensitive to climate change and human perturbation, is presented. The baseline value of aerosol optical depth (AOD) was 0.029 and 0.027 at Nam Co and QOMS, respectively, which are comparable to or even lower than those at some Arctic and remote ocean locations. The seasonality of AOD values were the order of spring > summer > wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 142 publications
3
41
0
Order By: Relevance
“…Similar patterns of multi-year-averaged seasonal variation in AOD over the three study regions were also observed using the AERONET data, which have high accuracy and are widely used in aerosol characteristics and satellite-based AOD inversion verification studies (Holben et al, 1998;Martonchik et al, 2004;Russell et al, 2010;Yang et al, 2019). Over the TP, the multi-year-averaged AOD reaches a maximum in April and a minimum in December, while the aerosol composition varies greatly at different sites (Cong et al, 2009;Pokharel et al, 2019). High AOD mainly occurs in spring, associated with the Arctic haze, and low AOD occurs in summer over the Arctic (Breider et al, 2014;Grassl and Ritter, 2019;Rahul et al, 2014).…”
Section: The Multi-year-averaged Seasonal Variation In Aodsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar patterns of multi-year-averaged seasonal variation in AOD over the three study regions were also observed using the AERONET data, which have high accuracy and are widely used in aerosol characteristics and satellite-based AOD inversion verification studies (Holben et al, 1998;Martonchik et al, 2004;Russell et al, 2010;Yang et al, 2019). Over the TP, the multi-year-averaged AOD reaches a maximum in April and a minimum in December, while the aerosol composition varies greatly at different sites (Cong et al, 2009;Pokharel et al, 2019). High AOD mainly occurs in spring, associated with the Arctic haze, and low AOD occurs in summer over the Arctic (Breider et al, 2014;Grassl and Ritter, 2019;Rahul et al, 2014).…”
Section: The Multi-year-averaged Seasonal Variation In Aodsupporting
confidence: 68%
“…As an important component, atmospheric aerosols play a crucial role in the Earth-atmosphere system (Garrett and Zhao, 2006;Ghan and Easter, 2006;Nabat et al, 2015;Wei et al, 2021;Xue et al, 2020). Aerosols have a variety of effects on Earth's climate, including the significant direct effect (Rap et al, 2013;Xing et al, 2017), indirect effect (Albrecht, 1989;Liu et al, 2019Liu et al, , 2020aRighi et al, 2011;Twomey, 1977;Zhao and Garrett, 2015) and semi-direct effect (Amiri-Farahani et al, 2017;Johnson, 2005;Koren et al, 2004). Meanwhile, different aerosol types often have different physical, chemical and optical properties, and the balance between cooling and warming depends to some extent on aerosol characteristics (Boucher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies have shown that the annual baseline values of AOD observed at the two stations are nearly equal and very low (0.029 at Nam Co and 0.027 at QOMS) 5 , which reflects the background aerosol loading. In some extreme events in April, the daily AOD at the two stations has a sharp increase by 10−20 times relative to the baseline values ( Supplementary Figs.…”
Section: Tp Aerosol Loadingmentioning
confidence: 97%
“…The AOD and Ångström exponent (AE; as a qualitative indicator of aerosol particle size, with low AE indicating coarse particles) can be used together to classify aerosol types into the clean continental background, dust, anthropogenic aerosols (e.g., from biomass burning) or else aerosol mixtures, with a unique criterion over the TP ( Supplementary Fig. 3) 5 . The anthropogenic and dust aerosols are respectively fine and coarse in size 29 .…”
Section: Tp Aerosol Loadingmentioning
confidence: 99%